English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

solve the system of equations by substitution there r two different ones
2x+y=-17
4x-8y=36

and the other one is
2y=8
x+3y+2z=19
y-4z=-4

2007-06-11 12:31:21 · 5 answers · asked by CHALEAH J 1 in Science & Mathematics Mathematics

5 answers

2x+y=-17
4x-8y=36

y = -17 -2x

4x -8(-17 -2x) = 36
4x + 136 + 16x = 36
20x = -100

x = -5


2y=8
y = 4

y-4z=-4
4 - 4z = -4

z = 2

x+3y+2z=19
x + 3(4) + 2(2) =19
x + 12 + 4 = 19

x = 3

2007-06-11 12:40:35 · answer #1 · answered by John S 6 · 1 0

For the first equation:
y = -17 - 2x (arrived through isolating y)

4x - 8 (-17 - 2x) = 36 (now substitute y for the above equation)
4x + 136 + 16x = 36
20x + 136 = 36
20x = -100

x = -5

y = -17 - 2(-5)
y = -17 + 10
y = -7

x = -5, y = -7

For the second equation, y is already given as 4 so you know have to just solve for x and z:
x + 3(4) + 2z = 19 (substitute y for 4)
x + 12 + 2z = 19
x + 2z = 7

y - 4z = 4
4 - 4z = 4 (substitute y for 4)
-4z = 0
z = 0

x + 12 + 2(0) = 19 (substitute z for 0)
x + 12 = 19
x = 7

x = 7, y = 4, z = 0

2007-06-11 12:45:23 · answer #2 · answered by meco031719 3 · 0 0

Let's look at the first problem.
First, solve the top equation for y:
y = -2x -17

Then substitute that into the second equation:
4x - 8*(-2x -17) = 36

Then solve that for x:
4x +16x +136 = 36
20x = 36 -136 = -100
x = -5

Then plug that x-value into y=-2x -17:
y = -2*(-5) - 17
y = 10 - 17
y = -7

The answer to the first problem is:
x = -5, y = -7.

For the second problem: solve the first equation for y:
y = 4

Substitute that into the other two equations:
x + 3*4 + 2z = 19
4 - 4z = -4

Grind through some algebra, and these become:
x + 2z = 7
z = 2

Substitute the z=2 into the x+2z=7 to get:
x + 2*2 = 7
x = 7-4 = 3

Your answer is: x=3, y=4, z=2.

Hope that clears it all up for ya.

2007-06-11 12:44:10 · answer #3 · answered by Bramblyspam 7 · 0 0

2x+y=-17 --> y = -17-2x
4x-8y=36
4x -8(-17-2x) = 36
4x +136 +16x = 36
20x = -100 --> x = -5 , so y = -7

2y=8 --> y=4
x+3y+2z=19 --> x+3*4+2*2=19 --> x = 3
y-4z=-4 --> 4-4z =-4 --> z = 2

2007-06-11 12:43:46 · answer #4 · answered by ironduke8159 7 · 1 0

put the first equation in terms of y.

meaning y = blah blah blah

then, where you see y in the 2nd equation plug in (blah blah blah). after doing this you should only see x's. then solve for the x.

lets say x = 2. plug x=2 into any of the original equations to get y

2007-06-11 12:35:44 · answer #5 · answered by Erin G 2 · 0 2

fedest.com, questions and answers